Occupational Health Hazards on Tobacco Farm Workers: A Systematic Review - Fakhriya, Dina; Widayanti, MPH., Apt., Ph.D., Anna Wahyuni; Wiedyaningsih, Chairun (Academic Hospital Journal, 2025)
Background: Tobacco farm workers are exposed to numerous occupational health hazards, involving chemical, biological, and physical concerns. These hazards can cause acute and chronic health problems, affecting workers’ well-being and productivity. Objective: This systematic review aims to integrate available information on occupational health hazards among tobacco farm workers, identify important risks, and provide feasible mitigation techniques. Methods: A systematic search was conducted in Scopus, ScienceDirect, and PubMed for studies published between 2015-2023. Inclusion criteria comprised reviewed articles focusing on occupational health hazards among tobacco farm workers. Studies were screened, and data were extracted according to PRISMA guidelines. The Joanna Briggs Institute (JBI) and Mixed Methods Appraisal Tool (MMAT) were used to assess quality for the Critical Appraisal Tool. Results: This review found five studies that highlighted major health hazards, such as green tobacco sickness (GTS) caused by nicotine exposure, pesticide poisoning, respiratory problems, musculoskeletal disease, and cancer. Risk factors include extended exposure, a lack of protective equipment, and poor working conditions were frequently noted. Preventive strategies, such as the use of personal protective equipment (PPE), education programs, and government policies, must be prepared. There are research gaps in long-term health impacts and gender-specific concerns among tobacco farm workers. Conclusion: Tobacco workers face several occupational health hazards, including green tobacco sickness (GTS), pesticide exposure, respiratory illnesses, and ergonomic issues that require several interventions for prevention.